Two-component thermally conductive compositions of silane-based polymers
By using fillers with specific moisture content in two-component silylated polymer adhesives to promote mixing and crosslinking of the composition, the problem of processability and crosslinking speed of silylated polymer adhesives in the prior art is solved, and rapid Cross-linking and efficient assembly extend battery life.
Patent Information
- Application Number
- CN202380044380.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-10
AI Technical Summary
During the mixing process, the existing two-component silylated polymer adhesives have processability problems due to the difference in hydrophilicity and hydrophobicity of water and silylated polymers, and the crosslinking reaction is not rapid enough, making it difficult to do without adding free water. It can achieve effective mixing and rapid cross-linking, affecting the battery life and efficiency of the assembly process.
The thermally conductive two-component composition provided by the filler (C) is employed with the thermally conductive two-component composition in the two-component silanized polymer composition (B) with the filler (C) with the composition The mixing of (B) ensures rapid cross-linking of the silylated polymer and achieves homogeneity and rapid reaction of the composition without the addition of free water.
Improves the cross-linking speed of silanized polymers and the processability of the composition, reduces water deposition on the mixer blades, allows manual application and limits the risk of sagging, extends the life of the battery and improves assembly efficiency.
Smart Images

Figure BDA0005164486780000051 
Figure BDA0005164486780000052 
Figure BDA0005164486780000061
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive two-component silanized polymer composition and also to its use, in particular for improving the service life of batteries. The present invention also relates to the use of a filler (C) having a specific moisture content for crosslinking a two-component silanized polymer composition without adding free water. Background Art
[0002] There are various polymer-based compositions on the market that can be used in many fields, especially as adhesives and / or mastics. Adhesives and mastics are used to assemble (or join or connect) two substrates that can be chosen from the most dissimilar materials.
[0003] For example, the polymer-based compositions may be used as adhesives and / or mastics in construction, shipbuilding, or the transportation sectors (eg, road, marine, rail, or aerospace transportation).
[0004] Compositions based on alkoxysilane-terminated polymers (also called silylated polymers) have the advantage of being isocyanate-free. These compositions therefore constitute an alternative to compositions based on isocyanate-terminated polyurethanes commonly found on the adhesives market, which are preferred from a toxicological point of view.
[0005] These compositions based on silylated polymers react crosslinking in the presence of moisture by hydrolysis of the alkoxysilane groups carried by the polymer followed by their condensation to form siloxane bonds (—Si—O—Si—) which link the polymer chains in a strong three-dimensional network.
[0006] Certain applications, especially battery manufacturing assemblies, require polymer-based compositions to have specific properties, especially in terms of thermal conductivity. In particular, since the recharging of a battery is generally accompanied by an increase in temperature, it is important to limit the increase as much as possible, which tends to degrade certain electronic device circuits or reduce the useful life of the battery. It is therefore important that the silanized polymer composition has sufficient thermal conductivity to mitigate these problems.
[0007] However, closed assemblies such as batteries do not allow sufficient air (and therefore moisture) to pass through for the cross-linking reaction of the silanized polymer to occur.
[0008] A two-component composition can be used as an adhesive, the composition comprising a silanized polymer to be crosslinked on the one hand, and water on the other hand. The two components of the adhesive are usually packaged separately in two compartments of a double cartridge. Then, when applied to a substrate to be assembled, the adhesive is distributed by extruding the two components, for example using a double cartridge gun and when obtaining a homogeneous mixture thereof, for example by connecting a static mixer to the double cartridge. The reaction of the component comprising the silanized polymer with the component comprising water allows the crosslinking of the silanized polymer.
[0009] However, water is hydrophilic, but silanized polymers are hydrophobic. Therefore, processability problems are caused during mixing of the components because it is difficult to mix components containing water with components containing silanized polymers, and water is generally retained on the stirrer blades.
[0010] There is therefore a need to provide two-component silanized polymer compositions which have both good thermal conductivity and good processability.
[0011] Furthermore, there is a need to provide thermally conductive two-component silanized polymer compositions that crosslink rapidly. This property can be evaluated by measuring the open time of the composition: the shorter the open time, the faster the composition crosslinks.
[0012] Furthermore, there is a need to provide a thermally conductive two-component silanized polymer composition that can be applied rapidly by means of a manual twin box while limiting the risk of sagging, especially in non-horizontal positions. Summary of the invention
[0013] The present invention relates to a thermally conductive two-component composition comprising:
[0014] - A composition (A) comprising:
[0015] o Silylated polymers, and
[0016] ○ Rheological agent (r1) selected from amide wax and / or
[0017] ○ Contains the following rheological agent (r2):
[0018] ■ from 1 to 40% by mass of a diurea (a), relative to the total weight of the rheological agent (r2), obtained by reacting a primary aliphatic amine with a diisocyanate having a molar mass of less than 500 g / mol, and
[0019] ■ from 60 to 99% by weight of a plasticizer (b), relative to the total weight of the rheological agent (r2), the plasticizer (b) being selected from alkyl phthalates, pentaerythritol tetravalerate, alkyl sulfonates of phenol, diisononyl-1,2-cyclohexanedicarboxylate, 3,3′-[methylenebis(oxymethylene)]bis[heptane], dioctyl carbonate and mixtures thereof,
[0020] The rheological agent (r2) is in the form of a suspension of solid particles of diurea (a) in a continuous phase of plasticizer (b), and
[0021] - A composition (B) comprising:
[0022] o at least 1% by weight of filler (C), relative to the total weight of composition (B), said filler (C) providing at least 0.0025% by weight of moisture, relative to the total weight of composition (B),
[0023] Composition (A) and / or composition (B) further comprises at least one thermally conductive filler.
[0024] The present invention also provides for the use of the thermally conductive two-component composition according to the invention as an adhesive and / or mastic.
[0025] Furthermore, the invention also relates to the use of the thermally conductive two-component composition according to the invention as an adhesive in the field of building construction, in the field of construction of means of transport, preferably motor vehicles, railway and aerospace industries, and in the field of shipbuilding.
[0026] The invention furthermore relates to the use of the thermally conductive two-component composition according to the invention for improving the service life of batteries, preferably rechargeable batteries.
[0027] The invention further relates to the use of a filler (C) having a moisture content of between 0.05% by weight and 5% by weight, relative to the total weight of the filler (C), for crosslinking a two-component composition comprising a composition (A) comprising a silanized polymer and a composition (B) comprising the filler (C) without addition of free water.
[0028] The invention furthermore relates to an article, in particular a battery, comprising the thermally conductive two-component composition according to the invention.
[0029] Finally, the invention relates to a process for assembling two substrates by adhesive bonding involving:
[0030] - coating the thermally conductive two-component composition according to the invention on at least one of the two substrates to be assembled, and then
[0031] - Bringing the two substrates into physical contact.
[0032] Surprisingly, it has been found that incorporating a filler (C) into composition (B) providing at least 0.0025% by weight of moisture, relative to the total weight of composition (B), not only allows an improved mixing of composition (A) with composition (B) and thus limits processability problems (especially limiting water deposition on the mixer blades), but also results in rapid crosslinking of the silanized polymer after contact with composition (A) without the need to add (free) water to composition (B). Furthermore, the thermally conductive two-component composition according to the invention can not only be easily applied by manual twin-box (without the need for a pneumatic gun), but also limits the risk of sagging (especially in non-horizontal positions). DETAILED DESCRIPTION
[0033] Therefore, the present invention relates to a thermally conductive two-component composition comprising:
[0034] - A composition (A) comprising:
[0035] o Silylated polymers, and
[0036] - A composition (B) comprising:
[0037] o at least 1% by weight of filler (C), relative to the total weight of composition (B), said filler (C) providing at least 0.0025% by weight of moisture, relative to the total weight of composition (B),
[0038] Composition (A) and / or composition (B) further comprises at least one thermally conductive filler, and
[0039] Composition (A) and / or composition (B), preferably composition (A), further comprises:
[0040] ○ Rheological agent (r1) selected from amide wax and / or
[0041] ○ Contains the following rheological agent (r2):
[0042] ■ from 1 to 40% by weight of a diurea (a), relative to the total weight of the rheological agent (r2), obtained by reaction of a primary aliphatic amine with a diisocyanate having a molar mass of less than 500 g / mol, and
[0043] ■ from 60 to 99% by weight of a plasticizer (b), relative to the total weight of the rheological agent (r2), the plasticizer (b) being selected from alkyl phthalates, pentaerythritol tetravalerate, alkyl sulfonates of phenol, diisononyl-1,2-cyclohexanedicarboxylate, 3,3′-[methylenebis(oxymethylene)]bis[heptane], dioctyl carbonate and mixtures thereof,
[0044] The rheological agent (r2) is in the form of a suspension of solid particles of diurea (a) in a continuous phase of plasticizer (b).
[0045] Silylated polymers
[0046] The term "silylated polymer" refers to a polymer comprising at least one alkoxysilane group. Preferably, the silylated polymer comprises at least one alkoxysilane group located at the terminal end of the polymer.
[0047] The silanized polymer is generally in the form of a more or less viscous liquid. Advantageously, the silanized polymer has a viscosity at 23°C ranging from 0.5 to 200 Pa.s, preferably from 5 to 120 Pa.s, more preferentially from 15 to 80 Pa.s, even more preferentially from 30 to 60 Pa.s.
[0048] The viscosity of the silanized polymer can be measured, for example, according to the Brookfield method at 23° C. and 50% relative humidity (needle S28).
[0049] In the context of the present invention, ranges of values are understood to mean including the limit values. For example, a range "between 0% and 25%" especially includes the values 0% and 25%.
[0050] Advantageously, the silylated polymer comprises at least one, preferably at least two, alkoxysilane groups of formula (I):
[0051]
[0052] in:
[0053] -R 4 represents a linear or branched alkyl group containing from 1 to 4 carbon atoms, and when p is equal to 2, the group R 4 Same or different,
[0054] -R 5 represents a linear or branched alkyl group containing from 1 to 4 carbon atoms, and when p is equal to 0 or 1, the group R 5 Same or different, two groups OR 5 may be joined in the same ring, and
[0055] - p is an integer equal to 0, 1 or 2, preferably equal to 0 or 1.
[0056] Preferably, the alkoxysilane groups of the silylated polymer are of formula (I), wherein:
[0057] -R 4 and R 5 each represents a methyl group, and
[0058] -p is equal to 0 or 1.
[0059] Advantageously, the silylated polymer has a number average molecular weight between 500 and 70,000 g / mol, preferentially between 1,000 and 60,000 g / mol, more preferentially between 2,000 and 50,000 g / mol.
[0060] The molar mass of the polymers can be measured by methods well known to those skilled in the art, for example by NMR or by size exclusion chromatography using polystyrene standards.
[0061] Advantageously, the silylated polymer has formula (II), (III) or (IV):
[0062]
[0063] in:
[0064] -R 4 , R 5 and p have the same meanings as in formula (I) described above,
[0065] -P represents a saturated or unsaturated polymeric radical with a linear or branched open chain or comprising one or more optionally aromatic rings, optionally comprising one or more heteroatoms such as oxygen, nitrogen, sulfur and / or silicon, preferably oxygen and / or nitrogen,
[0066] -R 1 denotes a saturated or unsaturated divalent hydrocarbon-based group containing from 5 to 15 carbon atoms, having a linear or branched open chain, or containing one or more optionally aromatic rings,
[0067] -R 3 denotes a linear or branched divalent alkylene group containing from 1 to 6 carbon atoms, preferably from 1 to 3 carbon atoms,
[0068] -X represents a member selected from -NH-, -NR 7 - or -S- divalent group,
[0069] -R 7 denotes a linear or branched alkyl group containing from 1 to 20 carbon atoms, and which may also contain one or more heteroatoms,
[0070] - f is an integer ranging from 1 to 6, advantageously from 2 to 5, preferentially from 2 to 4, even more preferentially from 2 to 3.
[0071] Advantageously, the silanized polymer has the formula (II), (III) or (IV), wherein P represents a polymer radical selected from polyethers, polycarbonates, polyesters, polyolefins, polyacrylates, polyether polyurethanes, polyester polyurethanes, polyolefin polyurethanes, polyacrylate polyurethanes, polycarbonate polyurethanes, segmented polyether / polyester polyurethanes, preferably selected from polyethers, polyurethanes and mixtures thereof, more preferably selected from polyethers.
[0072] Preferably, the silylated polymer has the formula (II'), (II"), (III') or (IV'):
[0073]
[0074] in:
[0075] -R 1 , R 3 , R 4 , R 5 ,X,R 7 and p have the same meanings as in formulae (II), (III) and (IV),
[0076] -R 2 denotes a saturated or unsaturated, linear or branched, divalent hydrocarbon-based group, which optionally contains one or more heteroatoms, such as oxygen, nitrogen, sulfur, silicon,
[0077] n is an integer, preferably n is such that the number average molecular weight of the silylated polymer is between 500 and 70,000 g / mol, more preferentially between 1,000 and 60,000 g / mol, even more preferentially between 2,000 and 50,000 g / mol.
[0078] In the silylated polymers of formula (II'), (II"), (III') or (IV') defined above, when the radical R 2 When one or more heteroatoms are included, the heteroatom(s) are not present at the ends of the chain. In other words, the divalent group R bound to the oxygen atom adjacent to the silylated polymer 2 The free valences of each originate from a carbon atom. 2 The main chain of is terminated at each end with a carbon atom which then has a free valence.
[0079] According to one embodiment, the silylated polymer is obtained from a polyol selected from polyether polyols, polyester polyols, polycarbonate polyols, polyacrylate polyols, polysiloxane polyols, polyolefin polyols and mixtures thereof, preferably from a diol selected from polyether diols, polyester diols, polycarbonate diols, polyacrylate diols, polysiloxane diols, polyolefin diols and mixtures thereof, more preferably from polyether diols. In the case of the polymers of formula (II'), (II"), (III') or (IV') described above, such diols can be obtained by the formula HO-R 2 -OH or H-[OR 2 ] n -OH means, where R 2 has the same meaning as in formula (II'), (II"), (III') or (IV').
[0080] According to one embodiment, when the silylated polymer has the formula (II') or (IV'), the group R 2 It can be selected from the following divalent groups, the following formula of which shows two free valencies:
[0081] -Derivatives of polypropylene glycol:
[0082]
[0083] -Polyesterdiol derivatives:
[0084]
[0085] - Derivatives of polybutadiene glycol:
[0086]
[0087] - Derivatives of polyacrylate diols:
[0088]
[0089] - Derivatives of polysiloxanediol:
[0090]
[0091] in:
[0092] -q means that the group R 2 The number average molar mass ranges from 100 g / mol to 48600 g / mol, preferably from 300 g / mol to 18600 g / mol, more preferably from 500 g / mol to 12600 g / mol,
[0093] -r and s represent the group R 2The number average molar mass range is from 100 g / mol to 48600 g / mol, preferably from 300 g / mol to 18600 g / mol, more preferably from 500 g / mol to 12600 g / mol, zero or a non-zero integer, it is understood that the sum of r+s is different from zero,
[0094] -Q 1 denotes a linear or branched, saturated or unsaturated aromatic or aliphatic divalent alkylene group preferably containing from 1 to 18 carbon atoms, more preferably from 1 to 8 carbon atoms,
[0095] -Q 2 denotes a linear or branched divalent alkylene group preferably containing from 2 to 36 carbon atoms, more preferably from 1 to 8 carbon atoms,
[0096] -Q 3 , Q 4 , Q 5 , Q 6 , Q 7 and Q 8 Independently of one another represent a hydrogen atom or an alkyl, alkenyl or aromatic group preferably containing from 1 to 12 carbon atoms, preferably from 2 to 12 carbon atoms, more preferably from 2 to 8 carbon atoms.
[0097] According to one embodiment, R 1 is selected from the following divalent radicals, the following formula of which discloses two free valencies:
[0098] a) Divalent groups derived from isophorone diisocyanate (IPDI):
[0099]
[0100] b) Divalent radicals derived from dicyclohexylmethane diisocyanate (H12MDI):
[0101]
[0102] c) Divalent radicals derived from the 2,4- and 2,6-isomers of toluene diisocyanate (TDI):
[0103]
[0104] d) Divalent radicals derived from the 4,4'- and 2,4'-isomers of diphenylmethane diisocyanate (MDI):
[0105]
[0106] e) Divalent radical derived from hexamethylene diisocyanate (HDI): -(CH2)6-
[0107] f) Divalent groups derived from m-xylylene diisocyanate (m-XDI):
[0108]
[0109] According to a preferred embodiment, the silylated polymer has the formula (II") (preferably wherein R 3 represents a divalent linear or branched alkylene group containing 3 carbon atoms) or (III'), preferably (III'), and the group R 2 Preferably it denotes a linear or branched divalent alkylene group containing from 2 to 4 carbon atoms, more preferably a linear or branched divalent alkylene group containing 3 carbon atoms, even more preferably an isopropyl group (of the formula -CH2-CH(CH3)-).
[0110] According to a particularly preferred embodiment, the silylated polymer is a polymer of formula (III') wherein:
[0111] -R 2 represents an isopropylidene group,
[0112] -R 5 represents a methyl group, and
[0113] -p is equal to 0.
[0114] The polymers of formula (II), (II') or (II") can be obtained according to the processes described, for example, in EP 2336208 and WO 2009 / 106699. Among the polymers corresponding to formula (II), mention may be made of:
[0115] - STP-E10 (available from Wacker-Chemie): having a number average molar mass of 8889 g / mol and containing two groups of formula (I) of the dimethoxy type (p equals 1 and R 4 and R 5 represents a methyl group) of the formula (II"), wherein R 3 represents a methyl group;
[0116] - STP-E30 (available from Wacker-Chemie): having a number average molar mass of 14493 g / mol and containing two groups of formula (I) of the dimethoxy type (p equals 1 and R 4 and R 5 represents a methyl group) of the formula (II"), wherein R 3 represents a methyl group;
[0117] - S XP 2636 (available from Bayer): having a number average molar mass of 15038 g / mol containing two groups of formula (I) of the trimethoxy type (p equals 0 and R 5 represents a methyl group), wherein R 3 Represents an n-propyl group.
[0118] The polymers of formula (III) or (III') are obtainable by hydrosilylation of polyether diallyl ethers according to the process described, for example, in EP 1 829 928. Among the polymers corresponding to formula (III), mention may be made of:
[0119] -Polymer MS 350 (available from Kaneka), which corresponds to two groups of formula (I) containing dimethoxy type (p equals 1 and R 4 and R 5 represents a methyl group);
[0120] -Polymer MS 260 (available from Kaneka), which corresponds to two groups of formula (I) containing dimethoxy type (p equals 1 and R 4 and R 5 represents a methyl group);
[0121] - polymer MS S303H (available from Kaneka), corresponding to a number-average molar mass of from 21 000 to 23 000 g / mol containing two groups of formula (I) of dimethoxy type (p equal to 1 and R 4 and R 5 represents a methyl group);
[0122] -Polymer MS 520 (available from Kaneka), which corresponds to two groups of formula (I) containing dimethoxy type (p equals 0 and R 5 represents a methyl group);
[0123] The polymers of formula (IV) or (IV') can be obtained, for example, by reaction of (one or more) polyols with one or more diisocyanates, followed by reaction with aminosilanes or mercaptosilanes. Processes for preparing polymers of formula (IV) or (IV') are described, for example, in EP 2 583 988. A person skilled in the art will know how to adapt the manufacturing processes described in said document in the case of using different types of polyols. Among the polymers corresponding to formula (IV), mention may be made of:
[0124] - 1050MM (available from Momentive): having a number average molar mass of 16393 g / mol containing two groups of formula (I) of the trimethoxy type (p equals 0 and R 5 represents a methyl group), wherein R 3 represents an n-propyl group;
[0125] - Y-19116 (available from Momentive): a polyoxyethylene glycol having a number average molar mass ranging from 15000 to 17000 g / mol containing two groups of formula (I) of the trimethoxy type (p equals 0 and R 5 represents a methyl group), wherein R 3 Represents an n-propyl group.
[0126] The content of silylated polymer in composition (A) may range from 3% to 40% by weight, preferably from 5% to 35% by weight, more preferably from 10% to 30% by weight, even more preferably from 14% to 28% by weight, in particular from 17% to 22% by weight, of the total weight of composition (A).
[0127] Rheological agent
[0128] The total content of rheological agents in composition (A) may range from 0.2 to 15 wt %, preferably from 1 to 10 wt % and more preferentially from 1 to 5 wt %, relative to the total weight of composition (A).
[0129] The total content of rheological agents in composition (B) may range from 0.2% to 15% by weight, preferably from 1% to 10% by weight and more preferentially from 1% to 5% by weight, relative to the total weight of composition (B).
[0130] Preferably, composition (A) and / or composition (B) comprises a rheological agent (r2). In particular, rheological agent (r2) is the only rheological agent in composition (A) and / or composition (B).
[0131] Preferably, the composition (A) comprises a rheological agent (r2). In particular, the rheological agent (r2) is the only rheological agent in the composition (A).
[0132] Advantageously, only composition (A) comprises a rheological agent, preferably a rheological agent (r2). In particular, rheological agent (r2) is the only rheological agent in composition (A).
[0133] Rheological agent (r1)
[0134] The term "amide wax" is understood to mean a wax comprising one or more compounds containing at least one amide group. In particular, amide waxes are obtainable from fatty acid(s) (e.g. ricinoleic acid) and (di)amine(s).
[0135] The amide wax is preferably micronized, that is to say it has an average particle size of less than 1 mm. Advantageously, the amide wax has an average particle size of less than 500 μm, preferably less than 100 μm, more preferentially less than 10 μm.
[0136] The average particle size advantageously corresponds to the d50 particle size, ie the maximum dimension of 50% by volume of the smallest particles, and can be measured by a particle size analyzer, in particular by laser diffraction on a Malvern machine (for example according to standard NF ISO 13320).
[0137] Unless otherwise indicated, the standards referred to throughout this patent application are those in effect on the filing date of this patent application.
[0138] Rheological agents of amide wax type are generally heat-activatable, that is to say that a temperature above room temperature (23° C.) may be required during the preparation of the composition according to the invention in order to activate them (in particular to activate their rheological properties).
[0139] The activation temperature depends on the rheological agent.
[0140] Preferably, the activation temperature of the rheological agent (r1) is less than or equal to 80°C, more preferentially less than 65°C, and even more preferentially less than 55°C.
[0141] Examples of commercially available amide waxes include those sold by Arkema. SLX or SLT' or available from Elementis AS8053 or MAX(EC No.:432-430-3).
[0142] Rheological agent (r2)
[0143] Advantageously, the rheological agent (r2) allows the diurea (a) to be obtained by reacting an n-alkylamine (a1) containing from 1 to 22 carbon atoms, preferably n-butylamine, with a diisocyanate (a2) of formula (V):
[0144] NCO-R 6 -NCO(V)
[0145] Where R 6 One selected from the following divalent groups, the following formula of which discloses two free valencies:
[0146] -i) a divalent group derived from isophorone:
[0147]
[0148] -ii) Divalent group 4,4'-methylenebis(cyclohexyl):
[0149]
[0150] -iii) a divalent group derived from toluene 2,4-diisocyanate (or 2,4-TDI) or from toluene 2,6-diisocyanate (or 2,6-TDI), each of which has the formula:
[0151]
[0152] -iv) a divalent group derived from diphenylmethylene 4,2'-diisocyanate (or 4,2'-MDI) or derived from diphenylmethylene 4,4'-diisocyanate (or 4,4'-MDI), each of which has the formula:
[0153]
[0154] -v) Hexamethylene group: -(CH2)6-
[0155] -vi) m-xylylene group:
[0156] and
[0157] -vii) Hexahydro-m-xylylene group:
[0158]
[0159] Preferably, the diisocyanate (a2) has the formula (V), wherein R 6 is a divalent group derived from 4,2'-MDI or 4,4'-MDI, preferably 4,4'-MDI.
[0160] According to a preferred embodiment, the diurea (a) is obtained by reacting n-butylamine with a diisocyanate (a2) of formula (V) wherein R 6 is a divalent group derived from 4,2'-MDI or 4,4'-MDI, preferably 4,4'-MDI.
[0161] As indicated above, the plasticizer (b) is selected from alkyl phthalates, pentaerythritol tetravalerate, alkyl sulfonates of phenol, diisononyl-1,2-cyclohexanedicarboxylate, 3,3′-[methylenebis(oxymethylene)]bis[heptane], dioctyl carbonate and mixtures thereof.
[0162] The alkyl phthalates are preferably formed from diisodecyl phthalate (DIDP), bis(2-propylheptyl)phthalate and mixtures thereof.
[0163] As pentaerythritol tetravalerate, mention may be made of the product sold by Perstorp under the trade name Products for sale.
[0164] As esters of alkylsulfonic acids and phenols, mention may be made of the products sold by the company Lanxess
[0165] As diisononyl 1,2-cyclohexanedicarboxylate, there may be mentioned the product sold by BASF under the name Hexamoll Products for sale.
[0166] 3,3'-[Methylenebis(oxymethylene)]bis[heptane] can be identified by its CAS number: 22174-70-5 and is also known by the trade name 2-ethylhexanal available from Lambiotte.
[0167] Finally, dicaprylyl carbonate (EC No.: 434-850-2) is available from BASF.
[0168] Advantageously, the rheological agent (r2) allows the plasticizer (b) to be selected from alkyl phthalates; preferably, the plasticizer (b) is selected from diisodecyl phthalate, bis(2-propylheptyl) phthalate and mixtures thereof; more preferentially, the plasticizer (b) is diisodecyl phthalate.
[0169] According to a preferred embodiment, the rheological agent (r2) consists of:
[0170] from 1 to 40% by weight, relative to the total weight of the rheological agent (r2), of a diurea (a) obtained by reaction of a primary aliphatic amine with a diisocyanate having a molar mass of less than 500 g / mol, and
[0171] - from 60 to 99% by weight of a plasticizer (b), relative to the total weight of the rheological agent (r2), the plasticizer (b) being chosen from alkyl phthalates, pentaerythritol tetravalerate, alkyl sulfonates of phenol, diisononyl-1,2-cyclohexanedicarboxylate, 3,3'-[methylenebis(oxymethylene)]bis[heptane], dicaprylyl carbonate and mixtures thereof,
[0172] The rheological agent (r2) is in the form of a suspension of solid particles of diurea (a) in a continuous phase of plasticizer (b), and diurea (a) and plasticizer (b) are as described above including embodiments.
[0173] Advantageously, the rheological agent (r2) comprises and preferably consists of from 5 to 30% by weight of diurea (a) and from 70 to 95% by weight of plasticizer (b), the percentages being relative to the total weight of said rheological agent (r2).
[0174] The diurea (a) and the plasticizer (b) are as described above including the embodiments.
[0175] The rheological agent (r2) used in the thermally conductive two-component composition according to the present invention can be prepared according to the process described below.
[0176] The reaction of aliphatic primary amine and diisocyanate is highly exothermic. In order to prevent the large amount of heat formed by the reaction from causing the decomposition of the formed diurea, before the aliphatic primary amine and diisocyanate are reacted together, they are each dissolved in a plasticizer (b), which is therefore used to discharge the heat formed by the reaction. The two solutions of aliphatic primary amine and diisocyanate in plasticizer (b) are advantageously introduced into the reactor via a syringe at a pressure of 40 to 200 bar, preferably 80 to 120 bar, respectively, and the two solutions are therefore contacted in a sprayed liquid state. The amount of the reagent preferably corresponds to a (number of moles of aliphatic primary amine) / (number of moles of diisocyanate) ratio of about 2. The diurea is produced by a reaction in the form of solid particles dispersed in a continuous phase of plasticizer b), and the Brookfield viscosity of the corresponding suspension measured at a temperature of 23°C is generally between 1 and 50 Pa.s, preferably between 10 and 25 Pa.s.
[0177] The term "about X" is intended to mean plus or minus 10% of the value of X.
[0178] Filler (C)
[0179] The filler (C) of the composition (B) contains residual moisture which allows hydrolysis of the alkoxysilyl groups of the silanized polymer, which advantageously results in crosslinking of the silanized polymer without the need to add water to the composition (B).
[0180] The filler (C) is different from the thermally conductive filler.
[0181] Incorporating this filler (C) into composition (B) advantageously provides a more homogeneous thermally conductive two-component composition. In particular, since composition (A) is hydrophobic, especially due to the presence of the silanized polymer, mixing with composition (B) is facilitated when water is provided by filler (C).
[0182] Advantageously, filler (C) provides at least 0.005% by weight, preferably at least 0.010% by weight, more preferentially at least 0.015% by weight of moisture relative to the total weight of composition (B).
[0183] Advantageously, filler (C) provides between 0.0025% and 1% by weight, preferably between 0.005% and 0.8% by weight, more preferentially between 0.010% and 0.5% by weight, even more preferentially between 0.015% and 0.2% by weight of moisture relative to the total weight of composition (B).
[0184] The moisture provided by the filler (C) can be determined by taking into account the filler (C) content of the composition (B), and the moisture content of the filler (C). For example, if the composition (B) comprises 5% of filler (C), relative to the total weight of the composition (B), and the filler (C) comprises 0.5% of moisture, relative to the total weight of the filler (C), then the filler (C) provides (5×0.5) / 100=0.025% of moisture, relative to the total weight of the composition (B).
[0185] Advantageously, the moisture content of filler (C) is between 0.05% and 5% by weight, preferably between 0.1% and 3% by weight, more preferentially between 0.10% and 2% by weight, relative to the total weight of filler (C).
[0186] The skilled person knows how to determine the moisture content of filler (C). The moisture content of filler (C) can be determined by electrochemically determining the equivalence point according to the Karl Fisher method. For example, the moisture content can be determined using the protocol described in Example 1 below.
[0187] The average particle size of filler (C) may range from 10 nm to 400 μm; preferably from 20 nm to 100 μm, more preferentially from 30 nm to 50 μm.
[0188] The average particle size advantageously corresponds to the d50 particle size, ie the maximum dimension of 50% by volume of the smallest particles, and can be measured by a particle size analyzer, in particular by laser diffraction on a Malvern machine (for example according to standard NF ISO 13320).
[0189] Advantageously, filler (C) is chosen from clay, talc, kaolin, gypsum, carbonate fillers, zeolites, expandable graphite and mixtures thereof.
[0190] Preferably, filler (C) is selected from carbonate fillers, zeolites, expandable graphite and mixtures thereof, more preferably selected from carbonate fillers, zeolites and mixtures thereof.
[0191] Advantageously, the carbonate filler is formed from alkali metal or alkaline earth metal carbonates and mixtures thereof; preferably, the carbonate filler is calcium carbonate or chalk, more preferentially calcium carbonate, in particular precipitated calcium carbonate coated with a fatty acid.
[0192] When calcium carbonate is coated with fatty acids, this can impart complete or partial hydrophobicity to the calcium carbonate particles. In addition, the fatty acid coating acts as a hydrophobic coating, which prevents the calcium carbonate from absorbing the components of the composition and rendering them ineffective. The hydrophobic coating of calcium carbonate can account for from 0.1 wt % to 3.5 wt %, relative to the total weight of the calcium carbonate.
[0193] Preferably, the fatty acid coating the calcium carbonate comprises or consists of more than 50% by weight of stearic acid, relative to the total weight of fatty acids.
[0194] Examples of precipitated calcium carbonate coated with fatty acids that may be mentioned include CCR-S10 (sold by Omya) or SV14 (sold by Specialty Minerals).
[0195] Advantageously, the zeolite is selected from synthetic zeolites of type A, X, and / or Y, preferably type A, and having and between, preferably of aperture.
[0196] According to a preferred embodiment, filler (C) is precipitated calcium carbonate coated with fatty acid and / or having The pore size of type A synthetic zeolite.
[0197] Advantageously, the content of filler (C) ranges from 1% to 25% by weight, preferably from 2% to 20% by weight, more preferentially from 4% to 15% by weight, even more preferentially from 6% to 11% by weight, relative to the total weight of composition (B).
[0198] Thermally conductive fillers
[0199] The thermally conductive filler allows the diffusion of heat due to its thermal conductivity value. In particular, the thermally conductive filler has a thermal conductivity greater than or equal to 3 W / mK, preferably greater than or equal to 5 W / mK, more preferentially greater than or equal to 10 W / mK.
[0200] The thermal conductivity of the conductive filler can be determined via any method known to a person skilled in the art. Advantageously, the thermal conductivity is determined according to standard ASTM D5740.
[0201] Advantageously, the thermally conductive filler is electrically insulating. The term "electrically insulating" means in particular an electrical conductivity less than or equal to 0.1 S / m at 23°C, preferably less than or equal to 0.01 S / m at 23°C.
[0202] Thermally conductive fillers allow the thermally conductive two-component composition according to the invention to be endowed with good thermal conductivity.
[0203] Thus, the thermal conductivity of composition (A) and / or composition (B) is advantageously between 0.5 and 3 W / mK, preferably between 1.0 and 2.0 W / mK, more preferentially equal to about 1.5 W / mK.
[0204] The thermal conductivity of compositions (A) and (B) is preferably determined using the ASTM D5470 method.
[0205] The moisture content of the thermally conductive filler is advantageously less than 0.05 wt. %, preferably less than 0.03 wt. %, relative to the total weight of the thermally conductive filler. The moisture content can be determined by electrochemically determining the equivalence point according to the Karl Fisher method, for example by the following protocol described in Example 1 hereinafter.
[0206] The at least one thermally conductive filler may be selected from aluminosilicates, alumina, aluminum hydroxide, aluminum nitride, boron nitride, zinc oxide, magnesium oxide and mixtures thereof, advantageously from aluminosilicates, alumina, aluminum hydroxide, boron nitride, zinc oxide, magnesium oxide and mixtures thereof, preferably from aluminosilicates, alumina, aluminum hydroxide and mixtures thereof, more preferably from aluminosilicates and mixtures thereof.
[0207] The thermally conductive filler is preferably of natural origin (ie, not synthetic).
[0208] The thermally conductive filler advantageously does not have at least The three-dimensional crystalline structure of the pore size.
[0209] Preferably, composition (A) and / or composition (B) comprises at least two thermally conductive fillers.
[0210] Advantageously, the total content of thermally conductive filler(s) in composition (A) ranges from 50% to 90% by weight, preferably from 60% to 87% by weight, more preferentially from 65% to 85% by weight, even more preferentially from 70% to 80% by weight, relative to the total weight of composition (A).
[0211] Advantageously, the total content of thermally conductive filler(s) in composition (B) ranges from 50% to 90% by weight, preferably from 60% to 87% by weight, more preferentially from 65% to 85% by weight, even more preferentially from 70% to 80% by weight, relative to the total weight of composition (B).
[0212] According to a preferred embodiment, compositions (A) and (B) each comprise at least one thermally conductive filler. Preferably, compositions (A) and (B) each comprise at least two thermally conductive fillers.
[0213] Advantageously, compositions (A) and (B) each have a thermal conductivity between 0.5 and 3 W / mK, preferably between 1.0 and 2.0 W / mK, more preferentially equal to about 1.5 W / mK.
[0214] Advantageously, the total content of thermally conductive filler(s) in each of the compositions (A) and (B) ranges from 50% to 90% by weight, preferably from 60% to 87% by weight, more preferentially from 65% to 85% by weight, even more preferentially from 70% to 80% by weight, relative to the total weight of each of the compositions (A) and (B).
[0215] According to one embodiment, composition (A) and / or composition (B), preferably compositions (A) and (B) each comprise at least two thermally conductive fillers, the thermally conductive fillers in the composition having different particle sizes. Advantageously, the difference in particle size d50 between the two thermally conductive fillers is between 3 μm and 25 μm, preferably between 5 μm and 20 μm, more preferentially between 10 μm and 14 μm.
[0216] The particle size d50 is the largest dimension of 50% by volume of the smallest particles, is well known to the person skilled in the art and can be measured by a particle size analyzer, in particular by laser diffraction on a Malvern machine (for example according to standard NF ISO 13320).
[0217] Adhesion promoter
[0218] Composition (A) and / or composition (B) may also comprise at least one adhesion promoter.
[0219] Advantageously, the adhesion promoter is chosen from amino-, mercapto- and epoxy-alkoxysilanes, preferably from aminoalkoxysilanes, more preferentially from aminotrialkoxysilanes, even more preferentially from aminotrimethoxysilanes, for example 3-aminopropyltrimethoxysilane.
[0220] As example of epoxyalkoxysilane, mention may be made of (3-glycidyloxypropyl)trimethoxysilane (also known as GLYMO).
[0221] Advantageously, the aminotrimethoxysilane is formed by: 4-amino-3,3-dimethylbutyltrimethoxysilane (for example Silquest A-Link 600 sold by Momentive), (3-aminopropyl)trimethoxysilane (for example AMMO) and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (e.g. sold by Evonik Preferably, the aminotrimethoxysilane is (3-aminopropyl)trimethoxysilane.
[0222] The content of adhesion promoter may range from 0.1% to 3% by weight, preferably from 0.2% to 2% by weight, and more preferentially from 0.5% to 1.5% by weight, relative to the total weight of composition (A).
[0223] The content of adhesion promoter may range from 0.1% to 3% by weight, preferably from 0.2% to 2% by weight, and more preferentially from 0.5% to 1.5% by weight, relative to the total weight of composition (B).
[0224] According to one embodiment, the content of adhesion promoter in each of compositions (A) and (B) ranges from 0.1% to 3% by weight, preferably from 0.2% to 2% by weight, and more preferentially from 0.5% to 1.5% by weight, relative to the total weight of each of compositions (A) and (B).
[0225] Advantageously, compositions (A) and / or (B) comprise at least one adhesion promoter.
[0226] Preferably, the adhesion promoter is only in composition (A).
[0227] Crosslinking catalyst
[0228] The composition (B) may further comprise a crosslinking catalyst.
[0229] The crosslinking catalyst may be any catalyst known to the skilled person for the condensation of silanols. Examples of such catalysts that may be mentioned include:
[0230] - organic titanium derivatives, such as titanium acetylacetonate (for example sold by Dorf Ketal AA75),
[0231] - Aluminum, such as aluminum chelates (e.g. sold by King Industries 5218),
[0232] - amines, such as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) or 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 2,2'-dimorpholine diethyl ether (DMDEE) and 1,4-diazabicyclo[2.2.2]octane (DABCO),
[0233] - Catalysts based on zinc carboxylates and DBU (e.g. sold by King Industries 670),
[0234] - tin-based catalysts, such as compounds derived from dioctyltin or dibutyltin; in particular dioctyltin oxide, dioctyltin diacetate, dioctyltin dilaurate, dioctyltin dicarboxylate, dibutyltin diacetylacetonate (DBTDAA), dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin oxide, or the reaction product of bis(acetoxy)dioctyltin with tetraethylorthosilicate, preferably the reaction product of bis(acetoxy)dioctyltin with tetraethylorthosilicate. Mention may be made, for example, of S-1 (sold by Kaneka), or TIB 425 or TIB 423 (sold by TIB Chemicals),
[0235] Advantageously, the crosslinking catalyst is a tin-based catalyst, for example derived from the reaction of bis(acetoxy)dioctyltin and tetraethylorthosilicate.
[0236] Preferably, the crosslinking catalyst is a tin-based catalyst selected from compounds derived from dioctyltin and dibutyltin; more preferably, the tin-based catalyst is derived from the reaction of bis(acetoxy)dioctyltin and tetraethylorthosilicate (CAS No.: 93925-43-0).
[0237] The content of the crosslinking catalyst may range from 0.01 to 1.5 wt %, preferably from 0.02 to 1.0 wt %, and more preferentially from 0.1 to 0.5 wt %, relative to the total weight of composition (B).
[0238] Advantageously, composition (B) comprises a crosslinking catalyst.
[0239] Flame retardants
[0240] Composition (A) and / or composition (B) may further comprise a flame retardant.
[0241] Preferably, the flame retardant is selected from triaryl phosphates, trialkyl phosphates and mixtures thereof, more preferably selected from tricresyl phosphate, tolylene diphenyl phosphate, tributyl phosphate, trioctyl phosphate, tri(2-ethylhexyl) phosphate, tri(chloroethyl) phosphate, tri(dichloropropyl) phosphate, tri(dibromopropyl) phosphate and mixtures thereof, even more preferably tolylene diphenyl phosphate.
[0242] The content of flame retardant may range from 1 to 20% by weight, preferably from 5 to 18% by weight, and more preferentially from 8 to 15% by weight, relative to the total weight of composition (B).
[0243] The content of flame retardant may range from 1 to 20% by weight, preferably from 5 to 18% by weight, and more preferentially from 8 to 15% by weight, relative to the total weight of composition (A).
[0244] The content of flame retardant in each of compositions (A) and (B) may range from 1% to 20% by weight, preferably from 5% to 18% by weight, and more preferentially from 8% to 15% by weight, relative to the total weight of each of compositions (A) and (B).
[0245] Advantageously, composition (A) and / or composition (B) comprises a flame retardant.
[0246] Preferably, the flame retardant is only in composition (B).
[0247] Other additives
[0248] The thermally conductive two-component composition according to the invention may further comprise at least one additive. The additive may be in composition (A) and / or (B). Preferably, the additive is selected from plasticizers, solvents and UV stabilizers and mixtures thereof.
[0249] Advantageously, the thermally conductive two-component composition according to the invention comprises a mixture of additives selected from plasticizers, solvents and UV stabilizers (or antioxidants).
[0250] For the purposes of the present invention, water is not considered a solvent.
[0251] The content of the additive may range from 0.1 to 10 wt %, preferably from 1 to 5 wt %, and more preferentially from 2 to 3 wt %, relative to the total weight of the thermally conductive two-component composition.
[0252] Advantageously, the thermally conductive two-component composition according to the invention comprises an additive selected from plasticizers.
[0253] The term "additive selected from plasticizers" refers to a plasticizer that can be the plasticizer (b) in the composition (B), and / or a plasticizer that can be the plasticizer (b) in the composition (A) when the composition (A) does not contain the rheological agent (r2), or a second plasticizer in the composition (A) other than the plasticizer (b) when the composition (A) contains the rheological agent (r2).
[0254] Preferably, an additive chosen from plasticizers is introduced into composition (B).
[0255] The additive selected from the plasticizers may be any plasticizer conventionally used in the field of adhesive compositions.
[0256] Preferably, the plasticizer is selected from:
[0257] - diisodecyl phthalate (e.g. sold by BASF DIDP),
[0258] - diisononyl phthalate (DINP) (e.g. sold by BASF N),
[0259] - Alkyl sulfonates of phenol (e.g. sold by Lanxess ),
[0260] - diisononyl hexahydrophthalate (e.g. Hexamoll sold by BASF ),and
[0261] - Pentaerythritol tetravalerate (e.g. Pevalen® sold by Perstorp TM ).
[0262] More preferably, the plasticizer is diisononyl hexahydrophthalate (CAS No.: 166412-78-8).
[0263] According to a preferred embodiment, the content of additives chosen from plasticizers ranges from 1 to 15% by weight, preferably from 2 to 10% by weight and more preferentially from 3 to 7% by weight, relative to the total weight of composition (B).
[0264] The thermally conductive two-component composition according to the invention may contain from 0% to 5% by weight of a solvent, preferably a solvent that is volatile at room temperature (a temperature of about 23° C.), relative to the total weight of the composition. The volatile solvent may be chosen, for example, from alcohols that are volatile at room temperature, such as ethanol or isopropanol. Preferably, the thermally conductive two-component composition contains from 0% to 1% by weight, and more preferentially from 0% to 0.5% by weight of a solvent, relative to the total weight of the composition.
[0265] Advantageously, the thermally conductive two-component composition according to the invention comprises up to 1% by weight, preferably up to 0.5% by weight, of one or more UV stabilizers (or antioxidants), relative to the total weight of the composition. UV stabilizers are typically introduced to protect the composition from degradation resulting from reactions with oxygen, which is easily formed by the action of heat or light. These compounds may include antioxidants capable of scavenging free radicals.
[0266] Advantageously, the UV stabilizer(s) (or antioxidants) are chosen from benzotriazoles, benzophenones, "hindered" amines such as bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (CAS No.: 41556-26-7), methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate (CAS No.: 82919-37-7), octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and mixtures thereof. Mention may be made, for example, of the products Irganox 1076 sold by BASF, 292, 765 or 770DF, Riasorb UV-123 sold by Rianlon, and Okabest CLX 50 sold by OKA.
[0267] Preferably, the UV stabilizer(s) (or antioxidants) are selected from hindered amines such as bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and mixtures thereof.
[0268] More preferably, the UV stabilizer (or antioxidant) is a mixture of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine.
[0269] Advantageously, the thermally conductive two-component composition according to the invention does not contain any moisture absorbers, in particular moisture absorbers selected from vinyltrimethoxysilane, vinyltriethoxysilane, alkoxyarylsilanes and p-toluenesulfonyl isocyanate.
[0270] Further features of the thermally conductive two-component composition according to the invention
[0271] Advantageously, the volume ratio of composition (A) to composition (B) is between 0.25 and 4, preferably between 0.5 and 2, more preferentially between 0.8 and 1.2, for example equal to 1.0.
[0272] Advantageously, composition (B) does not comprise any water.
[0273] The term "does not contain any water" means that the presence of water in the composition is due solely to the presence of moisture in the ingredients of the composition (no water is added).
[0274] Advantageously, composition (B) has a moisture content of less than 1% by weight, preferably less than 0.8% by weight, more preferentially less than 0.5% by weight, even more preferentially less than or equal to 0.2% by weight, relative to the total weight of composition (B).
[0275] The moisture content of composition (B) can be determined by adding the moisture content provided by each of the ingredients made therefrom. Preferably, only filler (C) has a significant moisture content, i.e. at least 0.05% by weight, relative to the total weight of filler (C). Therefore, the moisture content of composition (B) corresponds preferentially to the moisture content provided by filler (C).
[0276] According to one embodiment, the thermally conductive two-component composition according to the present invention comprises:
[0277] - from 3 to 40% by weight of silylated polymer in composition (A), relative to the total weight of composition (A),
[0278] - from 0.2 wt. % to 15 wt. % of rheological agent (r1) and / or (r2), preferably (r2) in composition (A) and / or in composition (B), preferably in composition (A), relative to the total weight of said composition (A) or (B),
[0279] - from 1% to 25% by weight of filler (C) in composition (B), relative to the total weight of composition (B), said filler (C) providing between 0.0025% and 1% by weight of moisture, relative to the total weight of composition (B),
[0280] - from 50% to 90% by weight of (one or more) thermally conductive fillers in each of compositions (A) and (B), relative to the total weight of compositions (A) and (B),
[0281] - from 0.1% to 3% by weight of adhesion promoter in composition (A) and / or in composition (B), preferably in composition (A), relative to the total weight of said composition (A) or (B),
[0282] - from 0.01% to 1.5% by weight of a crosslinking catalyst in composition (B), relative to the total weight of composition (B),
[0283] - from 1% to 20% by weight of flame retardant in composition (A) and / or composition (B), preferably in composition (B), relative to the total weight of said composition (A) or (B), and
[0284] - from 0.1% to 10% by weight, relative to the total weight of the thermally conductive two-component composition, of one or more additives chosen from plasticizers, solvents and UV stabilizers, and mixtures thereof,
[0285] The volume ratio of composition (A) relative to composition (B) is between 0.25 and 4.
[0286] Preferably, the thermally conductive two-component composition according to the invention consists essentially of the ingredients mentioned above. The term "consisting essentially of" means that the thermally conductive two-component composition according to the invention comprises less than 5% by weight, preferably less than 2% by weight, even more preferentially less than 1% by weight of ingredients other than the ingredients mentioned above, relative to the total weight of the composition.
[0287] The ingredients of this embodiment and their specific amounts are as described above, including the embodiments.
[0288] According to one embodiment, the thermally conductive two-component composition according to the present invention comprises:
[0289] - from 3 to 40% by weight of silylated polymer in composition (A), relative to the total weight of composition (A),
[0290] - from 0.2% to 15% by weight of rheological agent (r1) and / or (r2), preferably (r2), in composition (A), relative to the total weight of composition (A),
[0291] - from 1% to 25% by weight of filler (C) in composition (B), relative to the total weight of composition (B), said filler (C) providing between 0.0025% and 1% by weight of moisture, relative to the total weight of composition (B),
[0292] - from 50% to 90% by weight of (one or more) thermally conductive fillers in each of compositions (A) and (B), relative to the total weight of compositions (A) and (B),
[0293] - from 0.1% to 3% by weight of adhesion promoter in composition (A) and / or in composition (B), preferably in composition (A), relative to the total weight of said composition (A) or (B),
[0294] - from 0.01% to 1.5% by weight of a crosslinking catalyst in composition (B), relative to the total weight of composition (B),
[0295] - from 1% to 20% by weight of flame retardant in composition (A) and / or composition (B), preferably in composition (B), relative to the total weight of said composition (A) or (B), and
[0296] - from 0.1% to 10% by weight, relative to the total weight of the thermally conductive two-component composition, of one or more additives chosen from plasticizers, solvents and UV stabilizers, and mixtures thereof,
[0297] The volume ratio of composition (A) relative to composition (B) is between 0.25 and 4.
[0298] Preferably, the thermally conductive two-component composition according to the invention consists essentially of the ingredients mentioned above.
[0299] The ingredients of this embodiment and their specific amounts are as described above, including the embodiments.
[0300] According to a particular embodiment, the thermally conductive two-component composition according to the invention comprises:
[0301] - from 17 to 22% by weight of a silylated polymer in composition (A), relative to the total weight of composition (A), said silylated polymer preferably being a polymer of formula (III'),
[0302] - from 1% to 5% by weight of a rheological agent (r2) in the composition (A), relative to the total weight of the composition (A), said rheological agent (r2) comprising:
[0303] o from 5 to 30% by weight of a diurea (a) obtained by reaction of an n-alkylamine (a1) containing from 1 to 22 carbon atoms with a diisocyanate (a2) of formula (V), relative to the total weight of the rheological agent (r2), wherein R 6 is a divalent group derived from 4,2'-MDI or 4,4'-MDI, and
[0304] o From 70 wt % to 90 wt % of a plasticizer (b) selected from diisodecyl phthalate, bis(2-propylheptyl)phthalate, and mixtures thereof, relative to the total weight of the rheological agent (r2),
[0305] - from 6 to 11% by weight of filler (C), providing between 0.015% and 0.1% by weight of moisture in composition (B), the weight percentages being relative to the total weight of composition (B), filler (C) being selected from carbonate fillers, zeolites and mixtures thereof; in particular, filler (C) is precipitated calcium carbonate coated with fatty acids and / or having The pore size of the type of synthetic zeolite,
[0306] - from 70% to 80% by weight of thermally conductive filler(s) chosen from aluminosilicates and mixtures thereof in each of compositions (A) and (B), relative to the total weight of each of compositions (A) and (B),
[0307] - from 0.5% to 1.5% by weight of an adhesion promoter selected from aminotrimethoxysilanes in the composition (A), relative to the total weight of the composition (A),
[0308] - from 0.1% to 0.5% by weight of a crosslinking catalyst in composition (B), relative to the total weight of composition (B), said crosslinking catalyst being a tin-based catalyst,
[0309] - from 8 to 15% by weight of a flame retardant in composition (B), relative to the total weight of composition (B), the flame retardant being selected from tricresyl phosphate, cresyl diphenyl phosphate, tributyl phosphate, trioctyl phosphate, tri(2-ethylhexyl) phosphate, tri(chloroethyl) phosphate, tri(dichloropropyl) phosphate, tri(dibromopropyl) phosphate and mixtures thereof, and
[0310] from 2 to 3% by weight, relative to the total weight of the thermally conductive two-component composition, of one or more additives selected from plasticizers, solvents and UV stabilizers and mixtures thereof,
[0311] The volume ratio of composition (A) relative to composition (B) is between 0.8 and 1.2.
[0312] Preferably, the thermally conductive two-component composition according to the invention consists essentially of the ingredients mentioned above.
[0313] The ingredients of this embodiment and their specific amounts are as described above, including the embodiments.
[0314] Advantageously, the thermally conductive two-component composition according to the invention has very good reactivity, ie after mixing of the compositions (A) and (B) the crosslinking of the silanized polymer occurs rapidly.
[0315] This reactivity can be determined by measuring the “open time” of the thermally conductive two-component composition according to the invention.
[0316] The term "open time" refers to the time between the start of mixing of compositions (A) and (B) and the start of crosslinking of the thermally conductive two-component composition, during which time the user can apply the thermally conductive two-component composition to the substrate(s) to which he wishes to assemble it.
[0317] Preferably, the open time of the thermally conductive two-component composition according to the invention is less than 30 minutes, more preferentially less than or equal to 15 minutes.
[0318] The open time is preferably determined as described in Example 1 hereinafter.
[0319] Advantageously, the viscosity of the thermally conductive two-component composition according to the invention at 21° C. is less than or equal to 300,000 cP, preferably between 100,000 cP and 280,000 cP.
[0320] Advantageously, the viscosity of the thermally conductive two-component composition according to the invention at 21° C. is determined immediately after its production at 20 rpm (revolutions per minute) using a Brookfield RVT viscometer and a No. 7 needle.
[0321] The creep of the thermally conductive two-component composition according to the invention is advantageously less than 1 inch at 23° C. The creep can be determined according to standard ASTM D2202.
[0322] Preparation of the thermally conductive two-component composition according to the invention
[0323] Compositions (A) and (B) of the thermally conductive two-component composition according to the invention are each prepared separately by simple mixing of their constituents, preferably under vacuum.
[0324] The term “under vacuum” refers to a pressure below atmospheric pressure, advantageously between 10 kPa and 90 kPa, preferably between 50 kPa and 85 kPa, more preferentially between 60 kPa and 80 kPa.
[0325] Advantageously, the thermally conductive two-component composition according to the invention is prepared without the addition of free water, that is to say water other than the water inherently present in the ingredients of the composition.
[0326] According to a preferred embodiment, the composition (A) is prepared according to the following process:
[0327] - 1) mixing the silanized polymer with optional adhesion promoters and / or flame retardants and with optional additives such as plasticizers, solvents and UV stabilizers (or antioxidants) in a suitable container, preferably at a temperature between 18° C. and 28° C. and under vacuum, and then
[0328] -2) dispersing the optional (one or more) thermally conductive fillers in the aforementioned mixture at the same pressure until a homogeneous mixture is obtained, and then
[0329] -3) Add the optional rheological agent at the same pressure and homogenize the medium.
[0330] According to a preferred embodiment, the composition (B) is prepared according to the following process:
[0331] - 1) mixing optional adhesion promoters and / or flame retardants and optional additives such as plasticizers, solvents and UV stabilizers (or antioxidants), preferably at a temperature between 18° C. and 28° C. and under vacuum, and then
[0332] -2) dispersing filler (C) and optionally (one or more) thermally conductive fillers in the aforementioned mixture at the same pressure until a homogeneous mixture is obtained, and then
[0333] -3) adding the optional rheological agent at the same pressure and homogenizing the medium, and then
[0334] - 4) Add the optional crosslinking catalyst at the same pressure and homogenize the medium.
[0335] Preferably, the temperature during the preparation of composition (B) is less than or equal to 50°C, more preferentially less than or equal to 45°C, and even more preferentially less than or equal to 40°C.
[0336] Example 3 describes an example of the preparation of compositions (A) and (B) and a thermally conductive two-component composition according to the invention.
[0337] Compositions (A) and (B) can be packaged, for example, in a twin cartridge. Distribution of the thermally conductive two-component composition is advantageously carried out using a twin cartridge gun. A homogeneous mixture of the two components is obtained by connecting, for example, a static mixer to the twin cartridge.
[0338] Other subjects of the present invention
[0339] The invention furthermore relates to the use of the thermally conductive two-component composition according to the invention as adhesive and / or mastic, preferably as adhesive.
[0340] Furthermore, the present invention also relates to the use of the thermally conductive two-component composition according to the invention as an adhesive in the field of building construction, in the field of construction of means of transport, preferably motor vehicles, railway and aerospace industries, and in the field of shipbuilding, more particularly for assemblies intended for the production of batteries, especially rechargeable batteries for electric or hybrid vehicles.
[0341] The invention furthermore relates to the use of the thermally conductive two-component composition according to the invention for improving the service life of batteries, preferably rechargeable batteries.
[0342] The invention further relates to the use of a filler (C) having a moisture content of between 0.05% by weight and 5% by weight, relative to the total weight of the filler (C), for crosslinking a two-component composition comprising a composition (A) comprising a silanized polymer and a composition (B) comprising the filler (C) without addition of free water.
[0343] The term "free water" refers to water added to a two-component composition other than that inherently present in the ingredients of the composition.
[0344] Filler (C), composition (A), composition (B) and silanized polymer are advantageously as defined above, including the embodiments. In particular, filler (C) has a moisture content preferably between 0.1% and 3% by weight, more preferentially between 0.10% and 2% by weight, relative to the total weight of filler (C).
[0345] Advantageously, the two-component composition is a thermally conductive two-component composition as described above.
[0346] Advantageously, fillers (C) serve for rapid crosslinking of the two-component composition, ie the use of fillers (C) allows obtaining an open time for the two-component composition of less than 30 minutes, preferentially less than or equal to 15 minutes.
[0347] Opening hours are as defined above.
[0348] The invention furthermore relates to an article, in particular a battery, comprising the thermally conductive two-component composition according to the invention.
[0349] Preferably, the article according to the invention is a battery, in particular a rechargeable battery, more preferably a battery for an electric or hybrid car.
[0350] Finally, the invention relates to a process for assembling two substrates by adhesive bonding involving:
[0351] - applying the thermally conductive two-component composition according to the invention to at least one of the two substrates to be assembled, and then
[0352] - Bringing the two substrates into physical contact.
[0353] The substrates involved are very diverse and are, for example, inorganic substrates such as concrete, metals or alloys such as aluminum alloys, steel, non-ferrous metals and galvanized metals, or organic substrates such as wood, plastics such as PVC, polycarbonate, PMMA, polyethylene, polypropylene, polyester, epoxy resins, or substrates made of composites of metal and coated with paint (for example in the motor vehicle sector). Preferably, the substrate is metal and / or plastic.
[0354] All embodiments described above can be combined with one another. In particular, the various above-mentioned ingredients of the thermally conductive two-component composition according to the invention, and in particular the preferred embodiments, can be combined with one another.
[0355] The following examples are provided merely by way of illustration of the present invention and should not be construed as limiting the scope thereof.
[0356] Example
[0357] Embodiment 1: Ingredients and Measurement Methods
[0358] Ingredients used
[0359] Use the following ingredients:
[0360] -MS Polymer sold by Kaneka TM SAX 520: trimethoxysilane-terminated poly(propylene oxide) with a number average molar mass between 29,000 and 31,000 g / mol and a viscosity of 46 Pa.s;
[0361] -Sold by Evonik AMMO: (3-aminopropyl)trimethoxysilane (CAS No.: 13822-56-5), adhesion promoter;
[0362] -Sold by Specialty Minerals SV14: precipitated calcium carbonate coated with fatty acids, having an average particle size of 70 nm and a moisture content of 0.2% by weight, relative to the total weight of Calofort, filler (C);
[0363] - Riasorb UV-123 sold by Rianlon: bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate ((CAS No.: 129757-67-1), hindered amine light stabilizer (HALS);
[0364] - Tinuvin 770DF sold by BASF: bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (CAS No.: 52829-07-9), hindered amine light stabilizer (HALS);
[0365] - Neostann S-1 sold by Kaneka: product from the reaction of dioctyl bis(acetoxy)tin with tetraethyl orthosilicate (CAS No.: 93925-43-0), crosslinking catalyst;
[0366] - Marketed by BASF DINCH: diisononyl hexahydrophthalate, plasticizer;
[0367] - n-butylamine, aliphatic primary amine, for the preparation of rheological agent (r2);
[0368] - diisodecyl phthalate (DIDP) for the preparation of rheological agent (r2), plasticizer (b);
[0369] - 4,4'-diphenylmethane diisocyanate (4,4'-MDI) for the preparation of rheological agents (r2);
[0370] -Sold by Lanxess DPK: Cresyl diphenyl phosphate (CDP), flame retardant;
[0371] -Sold by Arkema SA 1720: Type A synthetic zeolite, with a pore size of and a moisture content of 1 wt %, based on the total weight of Siliporite, filler (C);
[0372] -Sold by The Minerals Engineers 1466-126 and 1466-506: Aluminosilicate, with d50 particle sizes of 21 μm and 9 μm, thermally conductive filler;
[0373] -Sold by Evonik 150: Fumed silica, rheological agent.
[0374] Measurement method
[0375] Each filler (C) SV14 and The moisture content of SA 1720) was determined using an 870KF Titrino Plus titrator and an 803TI vertical stirring module according to the Karl Fisher method as shown below.
[0376] The titrant is Hydranal - Composite 5 (sold by Honeywell), which contains 2-(2-ethoxyethoxy)ethanol and 4.5-5.5 mg of water per ml of titrant. The exact water content of the titrant is determined using a calibration solution containing 1 mg of water per gram of calibration solution (Hydranal sold by Honeywell). -CRM Water Standard 1.0), checked by using the titrator's "Titer Ipol" program.
[0377] The moisture content of the filler (C) is then determined using the titrator's "KFT Ipol" program. The first step in the program is an automatic adjustment step, in which about 50 mL of dry methanol (Hydranal -Dry methanol sold by Honeywell) is neutralized with a trace of water in the stirring module tank. Subsequently, a filler (C) of known mass (about 1 g) is placed in the tank, and the precise mass introduced is then entered into the program, and stirring is continued until the medium is homogeneous (about 1 to 10 min). Finally, the titration is performed automatically, and the moisture content of the filler (C) is displayed on the titrator screen.
[0378] Tensile strength and elongation at break are measured according to standard ISO 37 (2005) at a constant speed equal to 500 mm / min.
[0379] In particular, the following conditions apply:
[0380] A standard type-2 dumbbell shaped test piece was used, as set forth in the international standard ISO 37 (2005). The narrow portion of the dumbbell used had a length of 20 mm, a width of 4 mm, and a thickness of 3 to 4 mm.
[0381] To prepare the dumbbells, the test composition was placed in a Teflon mold and the composition was allowed to continue crosslinking under standard conditions (23° C. and 50% relative humidity) for 14 days.
[0382] The principle of the measurement consists in drawing a standard test piece in a tensile testing machine whose movable jaws are displaced at a constant speed equal to 500 mm / minute and recording:
[0383] - the elongation at break (expressed in %) is the elongation of the test piece corresponding to the extension observed at break, and
[0384] -Tensile strength (in MPa) is the tensile stress at which the specimen breaks.
[0385] Repeat the measurement of five test pieces and calculate the average value of the results obtained.
[0386] The open time is determined according to the skin-forming time. For this purpose, first a bead of cement (about 10 cm in length and 1 cm in diameter) is deposited on a cardboard carrier. Subsequently, the top of a pipette made of low-density polyethylene (LDPE) is used to contact the surface of the cement once every minute for a maximum of 2 hours to determine the exact time when the skin forms on the surface. The test is carried out under humidity and temperature controlled conditions (23°C and 50% relative humidity).
[0387] Creep is determined at 23° C. according to standard ASTM D2202 and self-smoothing is determined at 23° C. by applying a bead of the two-component composition of about 1 cm in diameter to a horizontal surface; if after 5 minutes the thickness of the bead is reduced to 7 mm or less, the composition is self-leveling.
[0388] The viscosity was determined immediately after production of the thermally conductive two-component composition at 20 rpm (revolutions per minute) and 21° C. using a Brookfield RVT viscometer and a No. 7 needle.
[0389] Thermal conductivity is measured according to standard ASTM D5470.
[0390] The flammability index is determined according to standard UL 94.
[0391] Embodiment 2: Preparation of rheological agent (r2)
[0392] Prepare two solutions:
[0393] - a solution A of n-butylamine in DIDP, consisting of 17.17% by weight of n-butylamine and 82.83% by weight of DIDP, the percentages being relative to the total weight of solution A, and then
[0394] -Solution B of 4,4′-MDI in DIDP, consisting of 29.46% by weight of 4,4′-MDI in 70.54% by weight of DIDP, the percentages being relative to the total weight of solution B.
[0395] The two solutions A and B are heated to 100° C. and then each introduced at a pressure of 100 bar into a reactor where they are sprayed continuously with one another in a weight ratio A / B=50.1 / 49.9, corresponding to an n-butylamine / MDI molar ratio equal to 2. The reaction is immediate and the temperature of the reactor reaches 140° C. at the end of the production.
[0396] At the reactor outlet, a stable 23.3% by weight (relative to the total weight of the dispersion) dispersion of a diurea in DIDP having the formula:
[0397]
[0398] The Brookfield viscosity of the suspension measured at 23°C was 15 Pa.s.
[0399] Embodiment 3: Composition 1 according to the present invention comprises composition 1A and composition 1B.
[0400] The various ingredients of each of compositions 1A and 1B were mixed in a stirred reactor in a plurality of steps according to the process described below, in the proportions indicated in Tables 1 and 2 below, respectively. The reactor was at room temperature (about 23° C.) before the addition of the ingredients, and the temperature could be raised as the ingredients were mixed. During the preparation of composition 1B, the temperature was advantageously controlled so as not to exceed 40° C.
[0401] The ingredients of Step 1 are mixed under vacuum (between 60 kPa and 80 kPa) at a stirring speed sufficient to homogenize.
[0402] Subsequently, the ingredients of step 2 are slowly added to the reactor used for step 1, again under vacuum and with a stirring speed sufficient for homogenization.
[0403] Finally, the ingredients of step 3 are added to the reactor, still under vacuum and with agitation speed sufficient to homogenize.
[0404] Table 1
[0405]
[0406] Table 2
[0407]
[0408]
[0409] By filler (C)( SV14) provides a moisture content of 0.02% by weight relative to the total weight of composition 1B.
[0410] Composition 1 according to the invention is then obtained by introducing compositions 1A and 1B into a twin box (protected from air and moisture) and then mixing them at room temperature (23° C.) in a volume ratio equal to 1.0 using a dynamic mixer connected to the end of the twin box.
[0411] Embodiment 4: Composition 2 according to the present invention comprises composition 2A and composition 2B.
[0412] The various ingredients of each of Compositions 2A and 2B were mixed in a stirred reactor in multiple steps according to the process described in Example 3 in the proportions indicated in Tables 3 and 4 below, respectively.
[0413] Table 3
[0414]
[0415] Table 4
[0416]
[0417] By filler (C)( SA 1720) provided a moisture content of 0.08% by weight relative to the total weight of composition 2B.
[0418] Composition 2 according to the invention is then obtained by introducing compositions 2A and 2B into a twin box (protected from air and moisture) and then mixing them at room temperature (23° C.) in a volume ratio equal to 1.0 using a dynamic mixer connected to the end of the twin box.
[0419] Embodiment 5: Comparative compositions 3 and 4
[0420] The respective ingredients of compositions 3A, 3B, 4A and 4B were mixed in a stirred reactor in multiple steps according to the process described in Example 3 in the proportions indicated in the following Tables 5 and 6, respectively (the percentages are weight percentages relative to the total weight of the respective corresponding compositions).
[0421] Table 5
[0422]
[0423] Table 6
[0424]
[0425] By filler (C)( SA 1720) provided a moisture content of about 0.08 wt. %, relative to the total weight of each of Compositions 3B and 4B.
[0426] Comparative composition 3 was then obtained by introducing compositions 3A and 3B into a twin box (protected from air and moisture) and then mixing them at room temperature (23° C.) in a volume ratio equal to 1.0 using a dynamic mixer connected to the end of the twin box.
[0427] Comparative Composition 4 was obtained using Compositions 4A and 4B in a similar manner.
[0428] Embodiment 6: Mechanical properties of compositions 1-2 according to the invention and comparative compositions 3-4
[0429] The mechanical properties (measured according to Example 1) of compositions 1-2 according to the invention and comparative compositions 3-4 are summarized in Table 7 below.
[0430] Table 7
[0431]
[0432] Compositions 1 and 2 according to the invention have very short open times (maximum 10 min). The compositions according to the invention therefore crosslink rapidly, however the moisture content provided by filler (C) is very low.
[0433] Furthermore, the thermal conductivity of compositions 1 and 2 according to the invention allows them to be used in particular in assemblies intended to manufacture batteries.
[0434] Finally, the viscosity of compositions 1 and 2 allows them to be easily applied by manual double box without the need for a pneumatic gun, and their low creep combined with the fact that they are not self-leveling enables them to be applied in non-horizontal positions while limiting the risk of sagging.
[0435] In contrast, Comparative Composition 3, which did not contain any rheological agent, had a creep of greater than 1 inch and was self-leveling, meaning that after application it would tend to "sag", even in a horizontal position; while Comparative Composition 4, which contained fumed silica as a rheological agent, had a viscosity that was too high to be easily applied by a manual two-box.
[0436] Compositions 1 and 2 according to the invention therefore have the advantage of being rapidly crosslinked without the addition of free water, being sufficiently thermally conductive and being easily applied by manual twin box while limiting the risk of sagging in a non-horizontal position.
Claims
1. A thermally conductive two-component composition comprising: - A composition (A) comprising: o Silylated polymers, and - A composition (B) comprising: o at least 1% by weight of filler (C), relative to the total weight of composition (B), said filler (C) providing at least 0.0025% by weight of moisture, relative to the total weight of composition (B), Composition (A) and / or composition (B) further comprises at least one thermally conductive filler, and Composition (A) and / or composition (B), preferably composition (A), further comprises: ○ Rheological agent (r1) selected from amide wax and / or ○ Contains the following rheological agent (r2): ■ from 1 to 40% by weight of a diurea (a), relative to the total weight of the rheological agent (r2), obtained by reaction of a primary aliphatic amine with a diisocyanate having a molar mass of less than 500 g / mol, and ■ from 60 to 99% by weight of a plasticizer (b), relative to the total weight of the rheological agent (r2), the plasticizer (b) being selected from alkyl phthalates, pentaerythritol tetravalerate, alkyl sulfonates of phenol, diisononyl-1,2-cyclohexanedicarboxylate, 3,3′-[methylenebis(oxymethylene)]bis[heptane], dioctyl carbonate and mixtures thereof, The rheological agent (r2) is in the form of a suspension of solid particles of diurea (a) in a continuous phase of plasticizer (b).
2. The thermally conductive two-component composition according to claim 1, wherein the silanized polymer comprises at least one, and preferably at least two, alkoxysilane groups of formula (I): -Si(R 4 ) p (OR 5 ) 3-p (I) in: -R 4 represents a linear or branched alkyl group containing from 1 to 4 carbon atoms, and when p is equal to 2, the group R 4 Same or different, -R 5 represents a linear or branched alkyl group containing from 1 to 4 carbon atoms, and when p is equal to 0 or 1, the group R 5 Same or different, two groups OR 5 may be joined in the same ring, and - p is an integer equal to 0, 1 or 2, preferably equal to 0 or 1.
3. The thermally conductive two-component composition according to claim 1 or 2, wherein the silanized polymer has the formula (II), (III) or (IV): in: -R 4 , R 5 and p have the same meanings as in formula (I) described above, -P represents a saturated or unsaturated polymeric radical with a linear or branched open chain or comprising one or more optionally aromatic rings, optionally comprising one or more heteroatoms such as oxygen, nitrogen, sulfur and / or silicon, preferably oxygen and / or nitrogen, -R 1 denotes a saturated or unsaturated divalent hydrocarbon-based group containing from 5 to 15 carbon atoms, having a linear or branched open chain, or containing one or more optionally aromatic rings, -R 3 denotes a linear or branched divalent alkylene group containing from 1 to 6 carbon atoms, preferably from 1 to 3 carbon atoms, -X represents a member selected from -NH-, -NR 7 - or -S- divalent group, -R 7 denotes a linear or branched alkyl group containing from 1 to 20 carbon atoms, and which may also contain one or more heteroatoms, - f is an integer ranging from 1 to 6, advantageously from 2 to 5, preferentially from 2 to 4, even more preferentially from 2 to 3.
4. The thermally conductive two-component composition according to claim 3, wherein the silanized polymer has the formula (II'), (II"), (III') or (IV'): in: -R 1 , R 3 , R 4 , R 5 ,X,R 7 and p have the same meanings as in formulae (II), (III) and (IV), -R 2 denotes a saturated or unsaturated, linear or branched, divalent hydrocarbon-based group, which optionally contains one or more heteroatoms, such as oxygen, nitrogen, sulfur, silicon, n is an integer, preferably n is such that the number average molecular weight of the silylated polymer is between 500 and 70,000 g / mol, more preferentially between 1,000 and 60,000 g / mol, even more preferentially between 2,000 and 50,000 g / mol.
5. The thermally conductive two-component composition according to any one of claims 1 to 4, wherein the rheological agent (r2) is such that the diurea (a) is obtained by reacting an n-alkylamine (a1) containing from 1 to 22 carbon atoms, preferably n-butylamine, with a diisocyanate (a2) of formula (V): NCO-R 6 -NCO(V) Where R 6 One selected from the following divalent groups, the following formula of which reveals two free valences: -i) a divalent group derived from isophorone: -ii) Divalent group 4,4'-methylenebis(cyclohexyl): -iii) a divalent group derived from toluene 2,4-diisocyanate (or 2,4-TDI) or from toluene 2,6-diisocyanate (or 2,6-TDI), each of which has the formula: -iv) a divalent group derived from diphenylmethylene 4,2'-diisocyanate (or 4,2'-MDI) or derived from diphenylmethylene 4,4'-diisocyanate (or 4,4'-MDI), each of which has the formula: -v) Hexamethylene group: -(CH2)6-, -vi) m-xylylene group: and -vii) Hexahydro-m-xylylene group:
6. The thermally conductive two-component composition according to any one of claims 1 to 5, wherein the filler (C) is selected from clay, talc, kaolin, gypsum, carbonate fillers, zeolites, expandable graphite and mixtures thereof.
7. The thermally conductive two-component composition according to any one of claims 1 to 6, wherein the filler (C) is a precipitated calcium carbonate coated with a fatty acid and / or having The pore size of type A synthetic zeolite.
8. The thermally conductive two-component composition according to any one of claims 1 to 7, wherein the at least one thermally conductive filler is selected from aluminosilicates, aluminum oxide, aluminum hydroxide, aluminum nitride, boron nitride, magnesium oxide and mixtures thereof, preferably from aluminosilicates, aluminum oxide, aluminum hydroxide and mixtures thereof, more preferably from aluminosilicates and mixtures thereof. 9 . The thermally conductive two-component composition according to claim 1 , wherein compositions (A) and (B) each comprise at least one thermally conductive filler.
10. A thermally conductive two-component composition according to any one of claims 1 to 9, wherein composition (A) and / or composition (B) further comprises a flame retardant, which is preferably selected from triaryl phosphates, trialkyl phosphates and mixtures thereof, more preferably selected from tricresyl phosphate, tolylene diphenyl phosphate, tributyl phosphate, trioctyl phosphate, tri(2-ethylhexyl) phosphate, tri(chloroethyl) phosphate, tri(dichloropropyl) phosphate, tri(dibromopropyl) phosphate and mixtures thereof, even more preferably tolylene diphenyl phosphate.
11. A thermally conductive two-component composition according to any one of claims 1 to 10, wherein the volume ratio of composition (A) to composition (B) is between 0.25 and 4, preferably between 0.5 and 2, more preferentially between 0.8 and 1.2, for example equal to 1.
0. 12 . Use of a thermally conductive two-component composition according to claim 1 for improving the service life of batteries, preferably rechargeable batteries.
13. Use of a filler (C) for crosslinking a two-component composition without adding free water, the filler (C) having a moisture content of between 0.05% by weight and 5% by weight, relative to the total weight of the filler (C), the two-component composition comprising a composition (A) comprising a silanized polymer and a composition (B) comprising the filler (C).
Citation Information
Patent Citations
Process for production of polyether polymers and compositions containing the polymers
EP1829928A1
Heat-curable adhesive composition
EP2336208A1
Polyurethane adhesive composition for producing agglomerates
EP2583988A1
Pressure-sensitive adhesives having a temperature-stable adhesive power
WO2009106699A2